Educating Future Agricultural Engineers at the University of Burgos, Spain, through a Service-Learning Project on Rural Depopulation and Its Social Consequences - Víctor Revilla-Cuesta; Marta Skaf; Javier Manso-Morato; José T. San-José; Vanesa Ortega-López (MDPI AG, 2023)
A Service-Learning Project (S-LP) is a teaching experience through which the concepts covered during an educational course can practically be applied to address a given social problem. It is therefore a useful teaching methodology to bring courses closer to the real world. An S-LP experience is reported in this paper that was conducted with students of agricultural engineering to address the problem of rural depopulation, through the design of agri-food buildings for industries, and economic activities that help to maintain a stable population. After the S-LP, a survey was administered to both students and teachers, to assess the success of this teaching experience. The responses of the students showed not only an awareness of the social problem that was addressed, but also a critical spirit that led them to seek the best possible answer, and a global vision of the issue. It helped them to reflect on all of its facets to arrive at a way of engaging with the social problem. Importantly, the students were able to reflect upon how engineers can also serve society through their technical knowledge. The teachers indicated that the S-LP motivated the students on the course, while enabling them to successfully learn the concepts, and to develop independent study skills searching for information. In general, an S-LP is an experience that the teachers in this study would recommend and that could be especially relevant for universities assuming a role as a social entity to heighten the visibility of social problems and needs.